Fundamentals in Modeling and Control of Mobile Manipulators - Li, Zhijun and Ge, Shuzhi Sam (Boca Raton : CRC Press, 2013)
Preface In the robotics and automation literature, mobile manipulators (manipulators mounted on mobile bases, platforms or vehicles) have received much attention since the beginning of the nineties in 20th century for its extended space of operation and extra degrees of freedom offered by the vehicle for accomplishing specific (typically , long range) manipulative tasks that otherwise could not be executed and accomplished. With a mobile platform, mobile manipulators can moving around and reach to places unfriendly to human beings, and perform operations at over a large space, or long range. Indeed, they can find a wide range of applications including (i) service or security applications at factories, offices, or homes, (ii) search and rescue operations in a harsh, demanding and/or dangerous environment, (iii) remote operations or explorations in remote place or space, and among others. Such systems combine the complementary advantages of mobile platforms and robotic arms for extend operational ranges an functionality, and at the same times bring along the complexity and difficulty in dynamic modelling and control system design for such a class of systems. One the one hand, mobile robotic manipulators possess strongly coupled dynamics of mobile platforms and robotic manipulators, not to mention the non-holonomic constraints introduced by the wheeled/tracked mobile platforms, which present much difficulties in the motion planning, control, coordination and cooperation of such systems. On the other hand, much advances in nonlinear system analysis and control system design offer powerful tools and fundamental concepts for the control of mobile manipulator systems--
1. Introduction -- 2. Kinematics and dynamics -- 3. Path planning and motion generation -- 4. Model-based control -- 5. Adaptive robust hybrid motion/force control -- 6. Under-actuated control -- 7. Coordination control -- 8. Cooperation control -- 9. Appendix.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Mobile robots; Manipulators (Mechanism); Electronic books